Crystallization and preliminary X-ray diffraction analysis of a myotoxic Lys49-PLA(2) from Bothrops jararacussu venom complexed with p-bromophenacyl bromide - Marchi-Salvador, D. P.; Fernandes, CAH; Amui, S. F.; Soares, A. M.; Fontes, MRM (Blackwell Publishing, 2006)
For the first time, a non-catalytic and myotoxic Lys49-PLA(2) (BthTX-I from Bothrops jararacussu venom) has been crystallized with BPB inhibitor. X-ray diffraction data were collected and electron-density calculations showed that the ligand is bound to the His48 residue. BthTX-I with His48 chemically modified by BPB shows strongly reduced myotoxic and cytotoxic activities. This suggests a biological correlation between the modification of His48, which is associated with catalytic activity of PLA(2)s, and other toxicological activities of Lys49-PLA(2)s.